Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I have recently read an article on imaginary numbers. It was very interesting, but left me with the above question. It had the answer in the question, it was $-1+7i$. But how do I calculate this?

share|improve this question
3  
Try using ordinary multiplication, replacing $i^2$ with $-1$ when needed. –  enzotib Sep 22 '12 at 7:47
    
Think of $3+4i$ as a pair of numbers $(3,4)$ with the multiplication rule $(a,b) \cdot (c,d) = (ac-bd, ad+bc)$. Then $(3+4i)\cdot (1+i) = (3,4) \cdot (1,1) = (-1,7) = -1+7i$. In particular, $i = (0,1)$ which gives $i^2 = (0,1)^2 = (-1,0) = -1$. –  copper.hat Sep 22 '12 at 8:10
add comment

3 Answers 3

up vote 4 down vote accepted

$(3+4i)\cdot(1+i)$

$= 3+4i+3i+4\cdot i^{2}$

$= 3+7i + 4\cdot i^{2}$

$i$ can be represented as ${\sqrt{-1}}$

So, ${i^{2} = -1}$

So, the above can be writen as :

$3+7i-4 = -1+7i$

share|improve this answer
    
Thanks a lot! Just didn't understand how i could be used in maths until today. –  imulsion Sep 22 '12 at 8:03
    
@enzotib: Thanks –  Sumit Bhowmick Sep 23 '12 at 4:27
    
Argh! That is a horribly non-standard use of $\Longrightarrow$. Please don't do that when you just mean $=$. –  Henning Makholm Sep 23 '12 at 13:46
1  
@HenningMakholm: I have edited –  Sumit Bhowmick Sep 28 '12 at 4:55
add comment

For complex numbers many of the rules for real numbers also hold. In particular the distributive law, so you can multiply out: \begin{align*} (3+4i)\cdot (1+i)&= 3\cdot (1+i) + 4i\cdot (1+i)\\ &= 3\cdot 1 + 3\cdot i + 4i\cdot 1+ 4i\cdot i\\ &= 3 + 3i + 4i + 4\cdot (-1)\\ &= -1 + 7i \end{align*}

share|improve this answer
    
I presume you meant 'rules for real numbers also hold'? –  copper.hat Sep 22 '12 at 8:11
    
Yes, thanks. Edited. –  Julian Kuelshammer Sep 22 '12 at 8:24
add comment

This is basic binomial multiplication. Using the fact that $(a + b)\cdot(c + d) = ac + ad + bc + bd $, we have,$$\begin{align}(3 + 4i)\cdot (1 + i) & = &3 + 3i + 4i + 4i^2 \\ & = & 4i^2 + 7i + 3\\ & = & 4(-1) + 7i + 3\\ & = & -4 + 7i + 3\\&=&7i - 1 \text{ which could be written as}-1+7i \end{align}$$*Important Note: In step 3, the fact that $i^2 = -1$ is used.*

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.